Development of animal models with chronic kidney disease-mineral and bone disorder based on clinical characteristics and pathogenesis - Tan, Biyu; Tang, Weili; Zeng, Yan; Liu, Jian; Du, Xiaomei; Su, Hongwei; Pang, Xianlun; Liao, Lishang; Hu, Qiongdan (Frontiers in Endocrinology, 2025)
Chronic kidney disease–mineral and bone disorder (CKD-MBD) is a systemic complication of chronic kidney disease (CKD), resulting in high morbidity and mortality. However, effective treatment strategies are lacking. The pathogenesis of CKD-MBD is unclear but involves feedback mechanisms between calcium, phosphorus, parathyroid hormone, vitamin D and other factors, in addition to FGF23, Klotho, Wnt inhibitors, and activin A. Construction of a perfect animal model of CKD-MBD with clinical characteristics is important for in-depth study of disease development, pathological changes, targeted drug screening, and management of patients. Currently, the modeling methods of CKD-MBD include surgery, feeding and radiation. Additionally, the method of CKD-MBD modeling by surgical combined feeding is worth promoting because of short time, simplicity, and low mortality. Therefore, this review based on the pathogenesis and clinical features of CKD-MBD, combined with the current status of animal models, outlines the advantages and disadvantages of modeling methods, and provides a reference for further CKD-MBD research.